(untitled) (Scientific Bulletin of the MPU School for Higher Studies, 2025)
The rule of article 75, section VIII, of Law 14.133/2021, previously provided for in section IV of article 24 of Law 8,666/1993, brought substantial changes to the waiver of bidding, by (i) allowing the maximum period for direct contracting due to emergency and public calamity to last up to one year and (ii) prohibiting recontracting based on the same triggering event. In a recent decision, the Honorable Supreme Federal Court declared the constitutionality of the final part of the provision, reinforcing the exceptionality of direct contracting and the rule of the bidding principle. Thus, the new legislation provides a protective shield by encouraging timely planning of the bidding process and reserving the exemption for exceptional cases, such as natural disaster situations, in addition to providing support for the Public Administration’s control in the application of the rule.